Effects of iron supplementation on total body hemoglobin during endurance training at moderate altitude - Friedemann, B.; Jost, J.; Rating, T.; Weller, E.; Werle, E.; Eckardt, K. U.; Bartsch, P.; Mairbaurl, H. (International Journal of Sports Medicine, 1999)
The aim of the study was to test the hypothesis that iron supplementation in well-trained non-iron-depleted athletes leads to an enhanced increase of total body hemoglobin (TBH) during training at moderate altitude. Therefore, the members of the national German boxing team were randomly assigned to treatment with ferrous-glycine-sulfate (1335 mg equivalent to 200mg elementary iron daily) or with placebo during 18 days of endurance training at moderate altitude (1800 m). Before and after altitude training TBH was determined by CO-rebreathing, measures of exercise performance were determined with an incremental treadmill test. Before, during and after the stay at moderate altitude erythropoietin (Epo), reticulocytes (Retics) and parameters of iron metabolism were measured in venous blood. The results show that TBH did not change significantly in the placebo-group and even slightly, but significantly decreased in the iron-treated group. However, there was a significant increase of Epo and Retics in both groups during training at moderate altitude whereas parameters of iron metabolism remained unchanged. VO2max did not change either. To test whether a training-induced hemolysis, an increased urinary iron excretion or gastrointestinal blood loss could explain the unexpected drop of TBH we tested most of the boxers again during a similar training camp at low altitude (400-1000 m) to obtain measures of hemolysis, urinary iron excretion and occult hemoglobin loss with the stools. Although there were signs of an increased erythrocyte turnover no iron loss could be observed. We conclude that 18 days of endurance training at an altitude of 1800 m does not lead to an increase of TBH in non-iron-depleted athletes with and without iron supplementation.